Pengaruh Media Sosial Terhadap Rasa Percaya Diri Remaja - Amaliyah, Shofwatun; Wijaya, Oei Joviana Claresta (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Adolescents' use of social media has grown ubiquitous, bringing with it opportunities and threats to their emotional and mental health. The purpose of this research is to examine how teens' self-confidence is affected by their use of social media. A survey method was used to gather data from teens within a particular age range. The results show that the more time spent on social media, the lower the self-confidence level. Teens' self-esteem takes a hit when they use social media to compare themselves to others' ideals of beauty, wealth, and lifestyle. Additionally, social validation in the form of likes, comments, and follower counts influences how teenagers perceive themselves. However, this study also finds that social media can have positive effects when used wisely, such as serving as a means of self-expression and identity building. Therefore, it is crucial for teenagers to have good digital literacy and support from their social environment to utilize social media healthily without compromising their self-confidence.